University social responsibility and academic social capital in Tunisia - Temporin, Simone (2016)
Revolutionary movements emerged from the “Arab spring” have determined undergoing socio-political changes in the region with significant implications and impacts on democratic transition and future sustainability. In this framework, the study explores Tunisian public universities’ social dimension and democratic implications of institutional partnerships in cooperation with local communities. In particular, it examines institutional, academic and students’ social responsibility as central elements of universities’ missions and students’ education. Existing complex dynamics linking social responsibility, social capital and democracy are considered within university contexts, taking also into consideration the role of Islam and Islamic values. In fact, university and students’ social responsibility have the potential to contribute to the redefinition of a post-revolution public sphere inspired by democratic participation and society-wide shared norms. Change in government policies affecting freedom of expression, restricted associational rights and political participation might result in institutional autonomy, allowing universities to fulfil their role in society while responding to economic and socio-cultural challenges.